STUDENTS' POINT OF VIEW ON THE USE OF WHATSAPP GROUP TO ELEVATE WRITING ABILITY - Evyta Tri Handayani; Dyah Aminatun (Journal of English Language Teaching and Learning, 2020)
English has been an important language nowadays. The role of the English language also has become the qualification of many people. However, many students state that English is not an easy language to master especially in Indonesia. Teachers also find it as a challenge in teaching English in Indonesia. They must have the appropriate technique and media for the students. One of the media that can be used by teachers to teach and engage students’ participation in learning English is WhatsApp. This application is also popular among the students as instructional learning mobile medium, including as a teaching medium to teach writing for students. Besides it is easy to operate, many students are familiar with it. This research aimed to find out students’ perspectives towards the use of WhatsApp group in improving students’ writing ability. This study applied a descriptive qualitative study with 37 students of the English Education study program as the participants. The data instrument used in this research were questionnaire and interview. The findings show that teaching writing by using the WhatsApp group can bring positive effects and benefit during the teaching and learning process. Besides that, it can also develop students’ writing ability. This result is supported by students’ opinions which state many good responses to this media rather than bad responses. Moreover, the result also shows that the WhatsApp group is one of the appropriate learning platforms for education in Indonesia.